Історико-картографічні матеріали до локалізації ряду неіснуючих церков у Перемишлі - Франків, Роман; Дідула, Ярослав; Frankiv, Roman; Didula, Yaroslav (Видавництво Львівської політехніки, 2021)
В статті узагальнено існуючі матеріали, що стосуються локалізації трьох культових будівель східно-християнської традиції Перемишля, місцезнаходження яких досі немає однозначного ствердження. На основі аналізу зібраних даних робиться спроба наблизитись до відповіді на питання про їхнє колишнє розташування та місце у містобудівельній структурі.

As a result of the analysis of descriptive, iconographic and cartographic material, the location of several non-existent temples of the Eastern Christian tradition in Przemyśl was determined and clarified. According to research, St. Trinity Church was located in a rectangle close to the square, now occupied by a residential building on Y. Slovatsky, 13 street (the so-called “rabbi's house”). Based on descriptions and cartographic materials, it is established that the locating of St. Michael Church on Pidzamche should consider significant changes in relief, which are associated with natural and anthropological factors. The most probable location of the building can be considered in the contemporary slope between the present highway № 28 and Senkevycha Street in the place of its deviation to the right. Thus, we can assume that the perspective of the street before this deviation once rested on the entrance to the missing temple. With the involvement of archaeological research, descriptive and illustrative interpretations of the so-called “obelisk of Jagiello”, it was determined that the location of the ancient church of St. Nikolas on Pidzamcha can be the area of houses No. 11 and No. 13 on Mateyka Street with probable variations, including a part of the present street.
Historical and cartographic matters for localization of a some of non-existent churches in Przemysl
Keywords: Перемишль; місцезнаходження; церква; іконографія; неіснуюча; Przemyśl; location; church; iconography; non-existent; 726